Consensus Regarding the Diagnosis, Prognosis and Treatment of Canine and Feline Mammary Tumors - 2019 - Cassali, Geovanni D.; Jark, Paulo C.; Gamba, Conrado; Damasceno, Karine A.; Estrela-Lima, Alessandra; Nardi, Andrigo B. De; Ferreira, Enio; Horta, Rodrigo S.; Firmo, Bruna F.; Sueiro, Felipe A. R.; Rodrigues, Lucas C. S.; Nakagaki, Karen Y. R. (Brazilian Journal of Veterinary Pathology, 2020)
The aim of this paper is to discuss and update criteria that can guide the diagnosis, prognosis and treatment of canine and feline mammary neoplasms. It was elaborated during the IV Mammary Pathology Meeting: Diagnosis, Prognosis and Treatment of the Canine and Feline Mammary Neoplasia, held on April 29th and 30th, 2019 in Belo Horizonte – MG, Brazil, sponsored by the Laboratory of Comparative Pathology of the Federal University of Minas Gerais (UFMG), with the support of the Brazilian Association of Veterinary Pathology (ABPV) and Brazilian Association of Veterinary Oncology (ABROVET). Academics from several regions of Brazil were present and contributed to this work.